2008
DOI: 10.1080/02678370801999651
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing and alcohol use: A cross-lagged longitudinal examination of the spillover hypothesis

Abstract: An area of concern for investigators and practitioners is the possible linkage between stressful workplace events and alcohol use and abuse; however, work in this area, specifically testing a ''spillover hypothesis,'' offers inconclusive evidence of a relationship between many work-based stressors and alcohol use. Using a three-wave panel sample (N0455) from a large US industrial firm that has undergone numerous downsizing events in the last decade, four alternative causal hypotheses using fully cross-lagged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Second, for every increase of one point on the job insecurity scale, the odds of high-risk drinking increase by 27%. Consistent with previous studies[ 28 , 37 , 43 ], this result suggests that job insecurity promotes stress and that high-risk alcohol consumption constitutes a coping strategy for attenuating the deleterious effects of work stressors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Second, for every increase of one point on the job insecurity scale, the odds of high-risk drinking increase by 27%. Consistent with previous studies[ 28 , 37 , 43 ], this result suggests that job insecurity promotes stress and that high-risk alcohol consumption constitutes a coping strategy for attenuating the deleterious effects of work stressors.…”
Section: Discussionsupporting
confidence: 91%
“…Some longitudinal studies have reported associations for occupations [ 25 29 ] and work-organization conditions. Decision latitude (skill utilization, decision authority)/job control [ 27 , 30 33 ]; social support [ 31 , 34 ]; job pride, stimulation, and paid training [ 35 ]; job satisfaction [ 28 ]; and job gratifications [ 25 , 26 , 36 , 37 ] have been shown to promote lower levels of alcohol intake, whereas psychological [ 30 , 32 ] and physical [ 30 , 38 ] demands; role overload [ 28 ]; working hours [ 39 ]; harassment [ 32 , 34 , 40 42 ]; and job insecurity [ 28 , 37 , 43 ] were associated with high-risk alcohol consumption. A weak relationship has also been reported for organizational justice [ 44 ], and at least one study reported an association for work-family conflicts [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…To that aim, we compared the cross-lagged correlations across two time points. This method is widely used in many areas of scientific research in the analysis of longitudinal data [52] , [53] , especially for identifying reciprocal influences of different cognitive abilities during development [54] , [55] . However, some authors have also pointed out the limits of this analysis and the need to interpret the differences between cross-lagged correlations with caution [56] .…”
Section: Discussionmentioning
confidence: 99%
“…The review revealed few studies of impacts on infections (79)-something warranting further research given the potential for presenteeism to exacerbate risks by encouraging workers to turn up when sick. On the other hand, a still small but growing number of studies have explored the association of downsizing and job insecurity with drug and alcohol use (66,125,126). Although management research has linked downsizing to bullying behavior by managers (127), the implications of this for workers' health and well-being has seldom been explored.…”
Section: Review Of Findings and Discussionmentioning
confidence: 99%